Pengaruh Brand Image, Atribut Produk, dan Persepsi Kualitas Terhadap Keputusan Pembelian Es Krim Mixue di Nagoya Thamrin Batam - Meiliana Meiliana; Inda Sukati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of brand image, product attributes, and perceived quality on purchasing decisions for Mixue ice cream in the Nagoya Thamrin area, Batam City. This study uses a quantitative approach with a descriptive research type. The population in this study were consumers who had purchased Mixue ice cream in Nagoya Thamrin Batam, with a sample size of 100 respondents determined through purposive sampling techniques and considering the Lemeshow approach to ensure the adequacy of the sample size. Data collection was carried out using a structured questionnaire, then analyzed through several stages of testing, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that the brand image variable had an influence on purchasing decisions, namely 14.8%, followed by product attributes with a contribution of 2.9%, and perceived quality contributed 30.3%. Simultaneously, the three independent variables were able to explain 14.3% of the variation in purchasing decisions based on the coefficient of determination (R²) value. Thus, the results of the study indicate that brand image and product attributes partially have no significant effect, while perceived quality partially has a significant effect on the purchase decision for Mixue ice cream. The results of the study simultaneously indicate that brand image, product attributes, and perceived quality collectively have a significant effect on the purchase decision for Mixue ice cream.